Impact on car platoon simulations: headway distance vs stopping distance - Lim, Jia Le (Nanyang Technological University, 2023)
Today, autonomous driving and intelligent transportation systems have attracted significant attention by virtue of the advanced management and monitoring systems with smart sensors and excellent information transformation based on Vehicle-to-X (or V2X) technology. Such emerging techniques provide a wealth of knowledge of the traffic conditions for all vehicles driving on an urban road network, which may reduce traffic congestion, fuel consumption, environmental footprints, and enhance safety. Considering the intelligence and safety of the vehicle design, connected automated vehicles (CAVs) have been proposed as the optimal choice for enabling road users to better drive with smart decisions in the complex traffic environment. However, coordination and interaction problems of CAVs are challenging issues due to the complex vehicle dynamics and unpredictable traffic conditions. Most notably, in a platoon of connected vehicles, time headway plays a vital role in both traffic capacity and road safety. It is desirable to maintain a lower time headway while satisfying string stability in a platoon since this leads to higher traffic capacity response to upcoming traffic conditions. However, if the time headway is too low, it may not satisfy anomalies and extreme cases. Thus, the goal is to present an anomaly and suggest an improvement to existing car platooning simulation frameworks for future reference.